Impact of different ultrasound-assisted processes for preparation of collagen hydrolysates from Asian bullfrog skin on characteristics and antioxidative properties - Indriani, Sylvia; Sae-leaw, Thanasak; Benjakul, Soottawat; Hong Quan, Tran; Karnjanapratum, Supatra; Nalinanon, Sitthipong (My University, 2022)
This study focused on impact of ultrasound-assisted process (UAP) at pre-treatment (UP) and simultaneous treatment (US) during papain hydrolysis for preparing collagen hydrolysate (CH) from Asian bullfrog skin. Ultrasonication times were varied (10, 20, 30 min), and CH prepared using papain hydrolysis without UAP was used as control. Different UAPs provided CH with various hydroxyproline contents, α-amino group contents, surface hydrophobicities, and antioxidative activities. UP at 20 min (UP-20) and US at 30 min (US-30) provided highly antioxidative CHs, which were selected for further studies on their Oxygen reactive absorbance capacity (ORAC) and molecular characteristics. CHs from UP-20 and US-30 had higher ORAC than that of control group (p ≤ 0.05). Slight difference in amino acid composition was detected between samples. Based on these results, molecular characteristic styles, molecular weight profile, antioxidative peptide content, and secondary structure of each sample were obtained. These results indicate that UP and US used varied enzymatic hydrolysis patterns and modified molecular conformation of CH, resulting in enhanced antioxidative activity. Therefore, different UAPs as UP and US could be effectively used in preparation of CH using papain hydrolysis from Asian bullfrog skin, which could improve production process efficiency by enhancing their bioactivity, particularly antioxidative activity.
Keywords: Antioxidative activities; Asian bullfrog skin; Collagen hydrolysate; Ultrasound pre-treatment; Ultrasound simultaneous treatment; Ultrasound-assisted processes